2019
DOI: 10.3390/polym11111760
|View full text |Cite
|
Sign up to set email alerts
|

Non-Chloride in Situ Preparation of Nano-Cuprous Oxide and Its Effect on Heat Resistance and Combustion Properties of Calcium Alginate

Abstract: With Cu2+ complexes as precursors, nano-cuprous oxide was prepared on a sodium alginate template excluded of Cl− and based on which the calcium alginate/nano-cuprous oxide hybrid materials were prepared by a Ca2+ crosslinking and freeze-drying process. The thermal degradation and combustion behavior of the materials were studied by related characterization techniques using pure calcium alginate as a comparison. The results show that the weight loss rate, heat release rate, peak heat release rate, total heat re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The combustion behaviors of the samples were studied using CONE, which is an effective performance-based and bench-scale method to evaluate flammability through simulating real-world fire conditions [36][37][38]. As shown in Figure 6a, overall, the heat release rate (HRR) value of CAS was lower than that of CA, which was in favor of slowing down the fire spread.…”
Section: Conementioning
confidence: 99%
“…The combustion behaviors of the samples were studied using CONE, which is an effective performance-based and bench-scale method to evaluate flammability through simulating real-world fire conditions [36][37][38]. As shown in Figure 6a, overall, the heat release rate (HRR) value of CAS was lower than that of CA, which was in favor of slowing down the fire spread.…”
Section: Conementioning
confidence: 99%
“…In addition to the signicant ame-retarding properties of metal hydroxides, metal oxides 38,39 also offer outstanding performance. 40 They are oen used as co-effectors, 41,42 with literature reporting special effects of transition metal oxides such as copper oxide, 43,44 nickel oxide 45 and so on. For example, Gogoi et al synthesised a vegetable oil alkyd resin with epoxy resin (EP) as the primary raw material from Jatropha curcas oil.…”
Section: Introductionmentioning
confidence: 99%
“…As a renewable biomass, it is preferable for its intrinsic features including non-toxic, well degradability and biocompatibility (Das et al 2017;Googerdchian et al 2012;Lee and Mooney 2012), and thus it has attracted great interest in recent years (Li et al 2017a, b;Liu et al 2015a;Senturk Parreidt et al 2018). Based on these reports, calcium alginate (CA) has been proved to be a desirable material for applications in the textile industry (Agnieszka Kyzioł; Mokhena and Luyt 2017a) due to its inert nature and good flame retardant property, although its mechanism still needs to be clarified (Shao et al 2019;Wang et al 2015). Noticeably, the studies have shown that the limiting oxygen index (LOI) value of CA was around 34, which is limited as a desirable flame-retardant agent.…”
Section: Introductionmentioning
confidence: 99%